POTENSI EKSTRAK METANOL BUNGA KECOMBRANG (Etlingera elatior) SEBAGI ANTIBAKTERI TERHADAP Escherichia coli DAN Pseudomonas aeruginosa PADA PASIEN INFEKSI SALURAN KEMIH - Yusianti Silviani; Sindi Noviana (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Urinary tract infection is an inflammation caused by bacterial proliferation, especially Escherichia coli as the main cause and Pseudomonas aeruginosa as a nosocomial cause. Torch ginger flowers (Etlingera elatior) can be used as an alternative natural antibiotic because they contain flavonoids, saponins, tannins, alkaloids, and steroids that have antibacterial potential. This study aims to determine the effectiveness of the inhibitory power of torch ginger flower methanol extract against Escherichia coli and Pseudomonas aeruginosa bacteria that cause urinary tract infections, and to analyze whether there is a significant difference in the inhibition zone at the extract concentration with the inhibition zone in the positive control ciprofloxacin. This study used a cross-sectional experimental analytical design. Extraction was carried out by the maceration method using methanol as a solvent. Phytochemical tests were used to identify active compounds, while antibacterial tests used the Kirby-Bauer disc diffusion method. The inhibition zone was measured using a caliper and analyzed by the Shapiro-Wilk, Kruskal-Wallis, and Mann-Whitney tests. The results showed that the extract positively contained flavonoids, saponins, tannins, alkaloids, and steroids, producing an inhibitory power of 6–8 mm on Escherichia coli and 6–7 mm on Pseudomonas aeruginosa, while ciprofloxacin produced 34 mm on Pseudomonas aeruginosa and 10 mm on Escherichia coli. There was a significant difference (p ≤ 0.05) between all extract concentrations and the positive control. In conclusion, the methanol extract of torch ginger flowers has antibacterial activity, but no concentration was able to match the effectiveness of ciprofloxacin.